The emergence of strategic budget initiatives - Nicol, Scherie (OECD Publishing, 2024)
The growth of strategic budget initiatives - such as gender budgeting and green budgeting - has been a prominent trend in OECD countries. This is driven by a desire to use the budget to help deliver transformational change in relation to key policy priorities demanding a whole-of-government response. This paper outlines the emergence of strategic budget initiatives across OECD countries and offers some preliminary observations on how these initiatives are being designed and implemented
Keywords: Finance and Investment; Governance; Economics